Delamanid: Safety and Efficacy Analysis - G. N. Mozhokina; A. G. Samoylova; I. A. Vasilyeva; A. V. Abramchenko (Туберкулез и болезни лёгких, 2023)
The review presents the analysis of 50 publications describing treatment of multiple drug resistant tuberculosis with regimens containing the new drug of delamanid. Delamanid possesses a dual bactericidal effect not only against active but also dormant Mycobacterium tuberculosis. The results of clinical studies on the efficacy and safety of delamanid within comprehensive chemotherapy are presented. The review demonstrates prospects for expanding the use of delamanid for treatment of adults and children.